Alcohol misuse by the young: problems and solutions - Skuse, David (Int Psychiatry, 2010)
Back in April 2006 (vol. 3, no. 2) we published papers on the theme of misuse of alcohol by young people, 3 years after the UK government had introduced the option of 24-hour drinking. The British Medical Association (BMA) subsequently recommended that there should be a programme of research to examine the consequences of this change to our drinking culture. In 2008, it reported on current trends in alcohol misuse (BMA Board of Science, 2008). An appendix to that report summarises the different alcohol control strategies pursued by the governments of England, Wales, Scotland and Northern Ireland in the past few years. These are outlined in the document Safe. Sensible. Social. The Next Steps in the National Alcohol Strategy (HM Government, 2007).